A house is not a home : FYP project book - Shafna (Nanyang Technological University, 2020)
A House Is Not A Home opens with Yasmine finding out from her mother, Hayati that her brother, Khai, had been arrested for drug abuse.The purpose of the film was to question society’s perception of what it meant to be an individual in the family unit. We achieved these objectives through creating complex characters like Yasmine who grapple with deciding between supporting her family and whether she should start thinking about her own life. We also will be showcasing the film on social media so that it can reach out to the masses.